An accelerator facility for WDM, HEDP, and HIF investigations in Nazarbayev University - Kaykanov M. I. Marat Islambekovich; Baigarin K. Kanat; Tikhonov A. A. Aleksandr Aleksandrovich; Urazbaev A. Arshat; Kwan J. Joe; Henestroza E. Enrique; Remnev G. E. Gennady Efimovich; Shubin B. G. Boris Grigorievich; Stepanov A. V. Andrey Vladimirovich; Shamanin V. I. Vitaly Igorevich; Waldron W. L. William L. (Lasers, Particle Beams, Fusion Technology, 2016)
Title screen